Gene promoter DNA methylation patterns have a limited role in orchestrating transcriptional changes in the fetal liver in response to maternal folate depletion during pregnancy. Issue 9 (6th June 2016) - McKay, Jill A.; Adriaens, Michiel; Evelo, Chris T.; Ford, Dianne; Mathers, John C.
Abstract : Nutrition during pregnancy influences the long‐term health of offspring. Possible mechanisms for this relationship are investigated by lowering the dietary supply of the B vitamin folate to pregnant dams, and changes in regulation of gene expression in the fetal liver are explored. DNA methylation was focused on, since this epigenetic mark can be altered by folate supply and is important in regulating transcription. It was found that 989 genes were differentially expressed and 333 promoters had altered DNA methylation but there was little overlap in affected genes. Abstract : Scope: Early‐life exposures are critical in fetal programming and may influence function and health in later life. Adequate maternal folate consumption during pregnancy is essential for healthy fetal development and long‐term offspring health. The mechanisms underlying fetal programming are poorly understood, but are likely to involve gene regulation. Epigenetic marks, including DNA methylation, regulate gene expression and are modifiable by folate supply. We observed transcriptional changes in fetal liver in response to maternal folate depletion and hypothesized that these changes are concomitant with altered gene promoter methylation. Methods and results: Female C57BL/6J mice were fed diets containing 2 or 0.4 mg folic acid/kg for 4 wk before mating and throughout pregnancy. At 17.5‐day gestation, genome‐wide gene expression and promoter methylation were measured by microarray analysis in male fetal livers. While 989 genes were differentially expressed, 333 promoters had altered methylation (247 hypermethylated, 86 hypomethylated) in response to maternal folate depletion. Only 16 genes had both expression and methylation changes. However, most methylation changes occurred in genomic regions neighboring expression changes. Conclusion: In response to maternal folate depletion, altered expression at the mRNA level was not associated with altered promoter methylation of the same gene in fetal liver.